Performance investigation of standalone wind power system equipped with sinusoidal PWM power inverter for household consumer in rural areas of Indonesia - Syahputra, Ramadoni; Purwanto, Kunnu; Soesanti, Indah (Elsevier, 2022)
This paper proposes the performance investigation of a standalone wind power system equipped with sinusoidal pulse width modulation (SPWM) power inverter for household consumption in rural areas of Indonesia. Indonesia, which is in the tropics, has the potential for developing wind power plants. One of the potential areas is the South Coast, Bantul, Yogyakarta Special Region, the location of this research. This work has designed, assembled, and tested a 4-kW wind power plant using a permanent magnet synchronous generator (PMSG) driven by a horizontal type of turbine. The test results show that the power plant can generate electrical energy suitable for meeting the electricity needs of residents’ homes. This success indicates that the generator's voltage is good enough and feasible to be stored in the battery. Although the voltage's value depends on the wind speed, it is adequate because it is close to the nominal voltage that the PMSG generator should produce. The electrical energy generated by this power plant is stored in the battery bank. Also, the performance of the SPWM power inverter has been demonstrated in the experimental tests of resistive and inductive loading. This power plant's development follows the government's commitment to utilizing renewable energy sources as priority energy as a strategy to reduce dependence on fossil energy and overcome the environment. © 2022 The Author(s)